Pengujian Sifat Fisika dan Listrik Minyak Kelapa Sebagai Alternatif Isolasi Pada Trafo Daya - Ni Made Seniari; Sumawarti Sumawarti; IK Wiryajati; Supriyatna Supriyatna; I.A.Sri Adnyani; Bagus Widhi Dharma.S (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
Transformer oil insulation material is the result of processes from petroleum, the material that is not able to be renewed, increasingly scarce, expensive, an imported commodity, and the need is increasing. So it is necessary to strive for alternative transformer oil that comes from renewable materials, based on domestic production, increases the added value of a commodity and environmentally friendly. The alternative transformer oil in this case is coconut oil. For this reason, it is necessary to test the feasibility of coconut oil as an alternative to transformer oil which includes testing of physical, chemical and electrical properties. The test results are compared with the standard transformer oil according to the IEC. The test results, the flashpoint and dielectric strength are feasible as an alternative to transformer oil, the density, volume expansion coefficient and viscosity of coconut oil are not suitable for use as an alternative to power transformer insulation oil. The percentage in terms of physical properties is 25%, with 4 tests of 10 existing physical properties. The feasibility of electrical properties is 50% with 1 test of 2 existing electrical properties.